1976
DOI: 10.1007/bf00509769
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism of vasoactive polypeptides by perfused rat liver

Abstract: Exsanguinated rat liver preparations perfused in situ with oxygenated saline solutions inactivated recirculating bradykinin (BK) at rates of 2.3 to 9.1 and isoleucyl5 angiotensin II (AII) at rates of 2.8 to 15.0 nmoles X min-1 X g-1 of liver, depending on the initial concentration of the peptides in the perfusion fluid (3.1 to 18.9 X 10(-6) M for BK and 8.5 to 17.0 X 10(-6) M for AII). On the other hand, at similar concentrations, recirculation of isoleucyl5 Angiotensin I (AI) for 8 min did not lead to decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
3

Year Published

1978
1978
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 16 publications
2
15
0
3
Order By: Relevance
“…As we could not observe any increase in the portal pressure, there were two possibilities: (i) the amount of angiotensin (1-7) produced is not enough to cause any effect or (ii) this peptide has no pressor effect in the intrahepatic circulation. To address this point, we administrated exogenous angiotensin (1)(2)(3)(4)(5)(6)(7) at concentrations that, in other vascular territories, are effective. 10 The lack of the hemodynamic effect of angiotensin (1-7) and the fact that its biological effects are not attributed to the binding to the AT1 and/or AT2 receptors reinforces the conclusion that the pressor effect induced by the injected AI is a consequence of its conversion to AII.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we could not observe any increase in the portal pressure, there were two possibilities: (i) the amount of angiotensin (1-7) produced is not enough to cause any effect or (ii) this peptide has no pressor effect in the intrahepatic circulation. To address this point, we administrated exogenous angiotensin (1)(2)(3)(4)(5)(6)(7) at concentrations that, in other vascular territories, are effective. 10 The lack of the hemodynamic effect of angiotensin (1-7) and the fact that its biological effects are not attributed to the binding to the AT1 and/or AT2 receptors reinforces the conclusion that the pressor effect induced by the injected AI is a consequence of its conversion to AII.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Recently we demonstrated that the PHR induced by AI is a consequence of its mandatory conversion into AII. 4 Although AII is the main active product of the RAS, there is evidence suggesting that AI or AII hydrolysis by peptidases other than the ACE generates biologically active peptides, mainly angiotensin (1)(2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…5B). Captopril has a small protecting effect in [pS 6 ]Bk clearance that probably occurs because the clearance of Bk in liver is done mainly by TOP [20,21] that is unable to hydrolyze [pS 6 ]Bk ( Table 2). The Bk portal hypertensive response is higher than that of [pS 6 ]Bk but its response lasts longer as can be evaluated by comparison of the areas under the curves as in Fig.…”
Section: Rat Liver Perfusionmentioning
confidence: 99%
“…Monovascular rat liver perfusion was performed as previously described [19][20][21]. Briefly, the rat was anesthetized with urethane (1.3 g/kg, i.p), the abdominal and thoracic cavities were opened and the portal vein and vena cava were cannulated.…”
Section: Monovascular Rat Liver Perfusionmentioning
confidence: 99%
“…Besides converting angiotensin (Ang) I in AngII, it is the major kininase involved in bradykinin degradation in the liver[10]. In 1976, Borges et al[11] showed that both AngI and AngII infused into the portal vein of a rat induced hypertensive effect, and they also demonstrated for the first time the conversion of AngI into AngII by the rat liver. This hypertensive response induced by AngII is mediated by AT1 receptor because when losartan was co-infused with AngII into the liver portal vein it abolished the hypertension response[12].…”
Section: Introductionmentioning
confidence: 99%